2007
DOI: 10.1002/jrs.1857
|View full text |Cite
|
Sign up to set email alerts
|

A new insight on the hydrogen bonding structures of nanoconfined water: a Raman study

Abstract: Water adsorbed in nanoporous silica glass has been investigated by Raman spectroscopy. The analysis was performed as a function of temperature (from +5 to +75°C), pore diameter (25 and 75Å) and by changing the nature of the substrate (from hydrophilic to hydrophobic) in order to understand the role played on the dynamic peculiarities of water arrangements both by the bare geometrical confinement and the specific interaction with surface. The experimental spectra, collected in the intra-molecular O-H stretching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 23 publications
1
67
0
Order By: Relevance
“…24,75,76 For example, Huang et al measured the Raman spectrum of H 2 O confined in 6.9 nm diameter Vycor glass and compared it to the bulk water spectrum. 24 They found that the key differences between bulk and confined water are a general blue-shifting of the spectrum along with the appearance of a shoulder on the high-frequency side.…”
mentioning
confidence: 99%
“…24,75,76 For example, Huang et al measured the Raman spectrum of H 2 O confined in 6.9 nm diameter Vycor glass and compared it to the bulk water spectrum. 24 They found that the key differences between bulk and confined water are a general blue-shifting of the spectrum along with the appearance of a shoulder on the high-frequency side.…”
mentioning
confidence: 99%
“…We also give Raman spectra of the bare mica for reference. All graphene spectra are monolayer, as determined by the peak height I 2D /I G ratio, 45 the 2D band position, and the 2D full width at half maximum (FWHM). 46 The dry transferred graphene possesses a G band at ω 53 The 2D band, however, shifts from ω 2D,b = 2651 cm -1 to ω 2D,a = 2666 cm -1 after the degas, the opposite direction of what is expected for the elimination of a p-type dopant.…”
mentioning
confidence: 99%
“…The spectra of M 1 and M 2 show a very strong and broad peak at 3330 cm À 1 for the hydroxyl (O-H) stretching vibration, while this peak of M 3 is weak. This may be due to the weak hydrogen bond interactions induced by the flexible hydrophobic chains [29]. From these results, it can be demonstrated that three types of membranes were prepared successfully as designed.…”
Section: Structural and Morphological Characterizationsmentioning
confidence: 91%